2006
DOI: 10.1002/j.2055-2335.2006.tb00601.x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Medicines Management Pathway

Abstract: Background: A novel medicines management pathway for patients with chronic heart failure was developed and commenced at the Prince of Wales Hospital in 2002. Aim: To evaluate whether the novel medicines management pathway facilitated by the community liaison pharmacist and medication management review facilitator helped implementation of home medicines reviews and improved medication management. Method: A survey of general practitioners, community pharmacists, accredited pharmacists and patients was conducted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Data were extracted from nine controlled studies (Table 1), 20-28 34 observational or uncontrolled studies with a focus on MRPs (Table 2), [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] and other clinical, humanistic and economic outcomes (Table 3), 10,44-61 11 qualitative (including interviews and focus groups) and nine survey research studies (Table 4). 11,13,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] Methodological quality of studies…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were extracted from nine controlled studies (Table 1), 20-28 34 observational or uncontrolled studies with a focus on MRPs (Table 2), [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] and other clinical, humanistic and economic outcomes (Table 3), 10,44-61 11 qualitative (including interviews and focus groups) and nine survey research studies (Table 4). 11,13,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] Methodological quality of studies…”
Section: Resultsmentioning
confidence: 99%
“…This included CMRs which involved pharmacist 22,44,53 Findings of qualitative work also supported these referral pathways, with stakeholders highlighting the use of pharmacists, nursing staff and other health providers as sources for CMR referrals. 63,64 Studies also reported CMRs undertaken by an accredited pharmacist working in a medical practice, 10,33,42,45 or as part of an ACAT (n ¼ 2), 23,51 community mental health team (n ¼ 1), 35,63 or palliative care team (n ¼ 1). 36 Six studies involved face-to-face case-conferences between the GP and pharmacist after CMR.…”
Section: Participant Characteristicsmentioning
confidence: 98%
“…In NSW a 'Heartlink' medication management pathway for patients with chronic heart failure was developed involving a community liaison pharmacist and medication management review facilitator [ 48 ]. On hospital admission, patient consent was obtained for the hospital pharmacist to communicate with the patient's preferred community pharmacy to obtain a complete medication history.…”
Section: Resultsmentioning
confidence: 99%